Farrow-to-Weaned Pig Cost-Return Budget - Dhuyvetter, Kevin C.; Tokach, Mike D. (My University, 2003)
This publication provides estimated cost and returns for a farrow-weaned pig operation.
MF2153_2003_10
Keywords: MF2153; Livestock; Economics; MF